The Emergence of Artificial Intelligence in Cardiology: Current and Future Applications - Kulkarni, Prashanth; Mahadevappa, Manjappa; Chilakamarri, Srikar (Current Cardiology Reviews, 2022)
Artificial intelligence technology is emerging as a promising entity in cardiovascular medicine, potentially improving diagnosis and patient care. In this article, we review the literature on artificial intelligence and its utility in cardiology. We provide a detailed description of concepts of artificial intelligence tools like machine learning, deep learning, and cognitive computing. This review discusses the current evidence, application, prospects, and limitations of artificial intelligence in cardiology.
Keywords: cardiovascular